PARENTAL ATTIUDE AS CONSTRAINT TO FAMILY VALUES ? - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This qualitative study aimed at exploring the need to instill familial values in the daily life of secondary school students. The study respondants comprise five secondary school teachers who teach five subjects related to the topic of the family. The researcher used the technique of semi-structured questionnaire, observations, video recording and document analysis in the process of data collection. The results showed that the issues of validity and trustworthiness can be managed through using four main methods, namely triangulation, peer review, audit trail and prolonged engagement. The Atlas software was used to analyse questionnaire transcription and construct the theme in this study. Results showed the parental factor as impeding the application of familial values in student life. Accordingly, parents need to play a pivotal role in instilling familial values in daily application that can serve as guides in the life of the family and society. Hence, all sides especially parents need to pay full attention and give priority to the elements of instilling familial values at home so as to ensure its implementation fulfills the needs of a challenging contemporary life.